Perbandingan Kinerja Algoritma Prefix Code C2 dan LZW Dalam Mengkompresi File Gambar - Raihan, Kevin; Pristiwanto, Pristiwanto (MEANS (Media Informasi Analisa dan Sistem), 2024)
Data compression plays a crucial role in reducing file sizes, particularly for image files, to conserve storage space and accelerate data transmission. This study eval_uates the performance of two widely-used compression algorithms: Prefix Code C2 and LZW, focusing on their effectiveness in compressing image files. The research involves a comparative analysis of the Prefix Code C2 and LZW algorithms based on several performance metrics, such as file size post-compression, compression speed, and decompression speed. The experimental results highlight that each algorithm has specific strengths and weaknesses depending on the image type and characteristics. The Prefix Code C2 algorithm demonstrates superior compression ratios for images with high levels of repetition, whereas the LZW algorithm outperforms in both compression and decompression speed for images with more intricate color variations. These insights can assist in selecting the most suitable compression algorithm for different types of image files.